2012
DOI: 10.1080/13504622.2011.634494
|View full text |Cite
|
Sign up to set email alerts
|

To know, to decide, to act: the young child’s right to participate in action for the environment

Abstract: This article draws on a research study that focused on young children's involvement in an environmental curriculum that created for them opportunities to display their competence and confidence through knowing, deciding and acting for the environment within a supportive early childhood setting. When young children are involved in making decisions that affect their lives, including those decisions regarding sustainability and the natural environment, they are capable in contributing to the decision-making that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0
31

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 16 publications
6
40
0
31
Order By: Relevance
“…Together, these findings support the argument that preschool and teachers may play an important role in developing children's declarative and functional knowledge through children's participation in discussion and involvement in sustainability-related issues. These findings are in line with previous environmental and sustainability-related studies, which demonstrated that children, with support and guidance from their teachers, learned about different local and global issues through their participation in the conversations and through being engaged in activities related to sustainability (Davis 2005;Lewis, Mansfield, & Baudains, 2010;Mackey, 2012). The results of our study also indicate that the mothers' and fathers' discussions and activities are differently associated, in terms of magnitude, with children's declarative and functional knowledge.…”
Section: Discussionsupporting
confidence: 89%
“…Together, these findings support the argument that preschool and teachers may play an important role in developing children's declarative and functional knowledge through children's participation in discussion and involvement in sustainability-related issues. These findings are in line with previous environmental and sustainability-related studies, which demonstrated that children, with support and guidance from their teachers, learned about different local and global issues through their participation in the conversations and through being engaged in activities related to sustainability (Davis 2005;Lewis, Mansfield, & Baudains, 2010;Mackey, 2012). The results of our study also indicate that the mothers' and fathers' discussions and activities are differently associated, in terms of magnitude, with children's declarative and functional knowledge.…”
Section: Discussionsupporting
confidence: 89%
“…The children at eco-certified schools seemed to have a deeper understanding of other children's economic situations in the world than those at non-eco-certified preschools. These findings are consistent with those of previous studies reporting that children who participated in whole-school programmes, such as eco-schools or schools that promote a healthy lifestyle, had a deeper understanding of these issues; furthermore, they learned about various global and local issues related to sustainability with support of their teachers (Davis, 2005;Davison, Davison, Reed, Halden, & Dillon, 2003;Lewis, Mansfield, & Baudains, 2010;Mackey, 2012). Nevertheless, two previous studies that compared eco-certified and non-eco-certified preschools in terms of children's knowledge and practices of environmental and sustainability issues using statistical analysis did not find any statistically significant differences (Borg, et al, 2017a(Borg, et al, , 2017b.…”
Section: Preschool Children's Level Of Justificationssupporting
confidence: 89%
“…Their findings revealed that the children sufficiently, through joint actions, conducted science investigations. Another study by Glynne Mackey (2012) on young children's decision-making touches upon sustainability and exposes various ways in which children act for the environment. In this research, imagination had a significant role in the children's meaning making.…”
Section: Previous Research On Imagination In Educationmentioning
confidence: 99%